The Influence Of Kip College Scholarships On Learning Motivation And Academic Achievement Of Stie Ganesha Management Study Program Students - Tohiroh Tohiroh; Riyawan Saputra; Neila Aisha; Syaban Maulana Alfarisi; Daffa Anisah Nabila; Farah Zhila Balqis (Journal on Education, 2025)
This study aims to analyze the effect of the KIP Lecture Scholarship on learning motivation and academic achievement of Management Study Program students at the Ganesha College of Economics (STIE). The KIP Lecture Scholarship is intended to help students from underprivileged families to better continue their higher education and focus on academic achievement. A quantitative approach was used in this study with a survey method, involving 25 KIP Kuliah Scholarship recipients as samples. Data was collected through a questionnaire designed to measure learning motivation and academic achievement. Data analysis used multiple linear regression to see the effect of the scholarship on both variables. The results showed that the KIP Kuliah Scholarship had a significant positive influence on students' learning motivation, which in turn had an impact on improving academic performance as measured by the Grade Point Average (GPA). This finding confirms that financial support through scholarships can improve students' learning focus and academic performance. The implications of this study are expected to help scholarship managers and universities in designing more effective programs to support students' academic success.